Differential diagnosis between oral fibroma and inflammatory hyperplasia: a proposal for histopathological criteria - Cristiano Macabu Badauy; Vinícius Coelho Carrard; Thaíse Gomes e Nóbrega; Felipe Nör; Márcia Gaiger de Oliveira; Manoel Sant'Ana Filho (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2013)
Oral Fibroma and Inflammatory Hyperplasia display similarities in their clinical and histopathological appearance. The present study proposed histopathological criteria for the differential diagnosis between those pathological entities. Histological sections of lesions histopathologically diagnosed as Oral Fibroma (n=61) and Inflammatory Hyperplasia (n=75) and were submitted to different techniques (Hematoxylin-Eosin; Masson Trichrome and Phosphomolybdic acid - Picrosirius red) to allow quantitative and qualitative analysis. The qualitative analysis of collagen density was based on sections stained by Hematoxylin-Eosin and focused in the center and periphery of each lesion. Wound and collagen fibers were more frequent and higher in Oral Fibroma, while parallel fibers were more frequent in Inflammatory Hyperplasia (Fisher's exact test, p